'Very great strife': the monks of Saint-Clément as competitors in twelfth-century Metz. Issue 5 (19th October 2020) - Herrick, Samantha Kahn
ABSTRACT: Dynamic growth sparked fierce competition in early twelfth-century Metz. One community vying to get ahead was the suburban Benedictine abbey of Saint-Clément. This article examines the competition the monks faced within Metz and traces how well they fared against their rivals. In particular, it shows that competition from other urban groups, both clerical and lay, was intense. It further reveals that disputes among these groups led to vandalism, forgery and legal wrangling as each party tried to win over the bishop, whose authority often decided the outcome of individual disputes. Under these circumstances, the monks of Saint-Clément did not achieve all their aims. Yet, the article argues, the monks' limited success is nevertheless significant. It reveals how stiff such intra-urban competition was, as well as the impact suburban monasteries could have on shaping the growing cities of medieval Europe.